2004
DOI: 10.1128/jcm.42.5.2279-2281.2004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation betweenHelicobacter pyloriOipA Protein Expression andoipAGene Switch Status

Abstract: Polyclonal antisera to either a synthetic OipA peptide or a recombinant OipA protein detected OipA expression in Helicobacter pylori and correlated with functional oipA status determined by PCR sequence (sensitivity and specificity of >94%). Immunoblotting is a simple and accurate method for detecting expression of the important virulence factor OipA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 13 publications
2
34
1
Order By: Relevance
“…Fifty microliters were plated onto Skirrow's plates with 5% sheep blood and incubated for 96 h under microaerobic conditions as described (4). OipA expression was determined by Western blot on bacterial lysates as previously described (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty microliters were plated onto Skirrow's plates with 5% sheep blood and incubated for 96 h under microaerobic conditions as described (4). OipA expression was determined by Western blot on bacterial lysates as previously described (18).…”
Section: Methodsmentioning
confidence: 99%
“…Expression of OipA is regulated by slipped strand mispairing within a CT rich dinucleotide repeat region located in the 5 ¶ region of the gene (13,16). Recent reports have shown that OipA coregulates proinflammatory cytokine expression and mediates adherence of H. pylori to gastric epithelial cells (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Immunoblotting-Anti-AlpA (AK214) (8), anti-AlpB (AK262) (9), anti-BabA (AK277) (18), and anti-OipA antisera (AK282) (19) were used as primary antibodies at a 1:5,000 dilution. Anti-CagA and anti-VacA antibodies (Austral Biologicals, San Ramon, CA) were used at a 1:3,000 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…The cag PAI is a 40-kb genome segment that encodes for f30 genes (1). OipA is an outer membrane protein of which the expression is transcriptionally regulated by a slipped-strand mispairing of the CT dinucleotide repeats in the 5 ¶ region of the gene (2,3). The majority of cag PAI-positive bacterial isolates are also OipA positive (4).…”
Section: Introductionmentioning
confidence: 99%